The meaning of philosophical activity in our context - Salazar, Freddy (Estudios de Filosofía, 1990)
The question about the meaning of philosophical activity in our context assumes that philosophy has a historical perspective that is determined by its relationship with society. It does not imply, moreover, that this is the only possible perspective of philosophical activity, because it is not possible to affirm, without ignoring the historiography of the philosophical discipline, that the only object or problem given to its reflection is the present of events historical. The history of philosophy leads us to recognize, in effect, the non-existence of a single object of philosophy and the experience, on the other hand, of problems of a very diverse nature that can be considered as "genuinely philosophical."